Editor's Choice – Meta-Analysis of Compliance with Endovascular Aneurysm Repair Surveillance: The EVAR Surveillance Paradox. (February 2023) - Antoniou, George A.; Kontopodis, Nikolaos; Rogers, Steven K.; Golledge, Jonathan; Forbes, Thomas L.; Torella, Francesco; Verhagen, Hence J.M.; Schermerhorn, Marc L.
Abstract : Objective: To compare the survival of patients who attended surveillance after endovascular aneurysm repair (EVAR) with those who were non-compliant. Data sources: MEDLINE and Embase were searched using the Ovid interface. Review methods: A systematic review was conducted complying with the PRISMA guidelines. Eligible studies compared survival in EVAR surveillance compliant patients with non-compliant patients. Non-compliance was defined as failure to attend at least one post-EVAR follow up. The risk of bias was assessed with the Newcastle–Ottawa scale, and the certainty of evidence using the GRADE framework. Primary outcomes were survival and aneurysm related death. Effect measures were the hazard ratio (HR) or odds ratio (OR) and 95% confidence interval (CI) calculated using the inverse variance or Mantel–Haenszel statistical method and random effects models. Results: Thirteen cohort studies with a total of 22 762 patients were included. Eight studies were deemed high risk of bias. The pooled proportion of patients who were non-compliant with EVAR surveillance was 43% (95% CI 36 – 51). No statistically significant difference was found in the hazard of all cause mortality (HR 1.04, 95% CI 0.61 – 1.77), aneurysm related mortality (HR 1.80, 95% CI 0.85–3.80), or secondary intervention (HR 0.66, 95% CI 0.31 – 1.41) between patients who had incomplete and complete follow up after EVAR. The odds of aneurysm rupture were lower in non-compliant patients (OR 0.63, 95% CI 0.39 – 1.01). The certainty of evidence was very low for all outcomes. Subgroup analysis for patients who had no surveillance vs. those with complete surveillance showed no significant difference in all cause mortality (HR 1.10, 95% CI 0.43 – 2.80). Conclusion: Patients who were non-compliant with EVAR surveillance had similar survival to those who were compliant. These findings question the value of intense surveillance in all patients post-EVAR and highlight the need for further research on individualised or risk adjusted surveillance.